Challenges In Regenerative Endodontics: A Case Report - Debkant Jena1, Sumit Dash1, Siba Prasad Jena2, Naomi Ranjan Singh2, Swapna Kumari3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Regenerative endodontics is a part of the advanced endodontic procedure for the well being of immatureteeth with root canals that are infected and it can be called as “paradigm shift” in the ideal approach oftreatment for continued root maturation and apical closure. It is a procedure which is clinically oriented todisinfect the root canal system without damaging stem cell present in the apical papilla and dentinal wall. Byinstrumentation process bleeding induced in the apical area to induced new stem cells in this area followedby intracanal cement placement to prevent microleakage. The mechanism of REP was to make triad bybiomarkers, stem cells, Scaffold which works on the regeneration of lost tissue of pulp dentine complexand further root formation. Many authors suggested that the REPS procedure is the definitive treatment ofimmature teeth with pulp necrosis.For a dentist it is a unique challenge to treat an immature tooth with apical periodontitis and pulpal necrosis.For endodontic treatment the options available are apexification, apical barriers and revascularization of thepermanent tooth. 16 years old boy comes to a comprehensive college clinic with the complaint of pain andswelling in the lower posterior tooth region. On clinical examination lower premolar with apical periodontitiswas treated with revascularization protocol irrigating with normal saline and sodium hypochlorite, anantibiotic paste (triple), mineral trioxide aggregate and then a coronal seal with a dental composite. Ina follow up of one year there was an evident resolution of radiolucencies in the periapical area and rootdevelopment was appreciated.